Ultrathin 2D nickel zeolitic imidazolate framework nanosheets for electrocatalytic reduction of CO2. Issue 77 (11th September 2019) - Wu, Jian-Xiang; Yuan, Wei-Wen; Xu, Ming; Gu, Zhi-Yuan
Abstract : The FE of CO increased from 33.7% of bulk Ni(Im)2 to 78.8% of 2D Ni(Im)2 -5 nm, which showed that the thinner the MOF nanosheets, the higher the catalytic selectivity. Abstract : Ultrathin 2D nickel(II) (Ni 2+ ) and imidazole (Im) based zeolitic imidazolate framework Ni(Im)2 nanosheets are reported as exceptional efficient electrocatalysts for the electrocatalytic CO2 reduction reaction. Five nanometre thick nanosheets have a higher faradaic efficiency of 78.8% and a surface active site density of 1.68 × 10 −7 mol cm −2, which is superior to those of thicker nanosheets and bulk Ni(Im)2 .